Elevated Levels of miR-144-3p Induce Cholinergic Degeneration by Impairing the Maturation of NGF in Alzheimer’s Disease - Zhou, Lan-Ting; Zhang, Juan; Tan, Lu; Huang, He-Zhou; Zhou, Yang; Liu, Zhi-Qiang; Lu, Youming; Zhu, Ling-Qiang; Yao, Chengye; Liu, Dan (Frontiers in Cell and Developmental Biology, 2021)
Cholinergic degeneration is one of the key pathological hallmarks of Alzheimer’s disease (AD), a condition that is characterized by synaptic disorders and memory impairments. Nerve growth factor (NGF) is secreted in brain regions that receive projections from the basal forebrain cholinergic neurons. The trophic effects of NGF rely on the appropriate maturation of NGF from its precursor, proNGF. The ratio of proNGF/NGF is known to be increased in patients with AD; however, the mechanisms that underlie this observation have yet to be elucidated. Here, we demonstrated that levels of miR-144-3p are increased in the hippocampi and the medial prefrontal cortex of a mouse model of AD mice. These mice also exhibited cholinergic degeneration (including the loss of cholinergic fibers, the repression of choline acetyltransferase (ChAT) activity, the reduction of cholinergic neurons, and an increased number of dystrophic neurites), and synaptic/memory deficits. The elevated expression of miR-144-3p specifically targets the mRNA of tissue plasminogen activator (tPA) and reduces the expression of tPA, thus resulting in the abnormal maturation of NGF. The administration of miR-144-3p fully replicated the cholinergic degeneration and synaptic/memory deficits observed in the mouse model of AD. The injection of an antagomir of miR-144-3p into the hippocampi partially rescued cholinergic degeneration and synaptic/memory impairments by restoring the levels of tPA protein and by correcting the ratio of proNGF/NGF. Collectively, our research revealed potential mechanisms for the disturbance of NGF maturation and cholinergic degeneration in AD and identified a potential therapeutic target for AD.